OPTIMIZATION OF POWDER MASS MIXING TIME AND TABLETTING PROCESS OF CHOLECALCIFEROL CHEWABLE TABLET - Purnama, Handi
Cholecalciferol or vitamin D3 is fat soluble vitamin that can help the absorption of calcium and phosphorus in the body and functions to maintain bone health and density. In the conditions of the Covid-19 pandemic, vitamin D is associated with a protective effect on the respiratory tract which can reduce the risk of infection and death from Covid-19. Based on the injunction of the Head of BPOM RI and ASEAN guidelines, the maximum daily limit for vitamin D is 1000 IU, which is equivalent to 25 micrograms. Therefore, a 1000 IU cholecalciferol product was developed with a chewable tablet dosage form according to the comparator product. The starting material used was cholecalciferol concentrate powder with a content of 100000 IU per gram due to its small dosage. The method used is the direct compression method because cholecalciferol is sensitive to moisture, air, and light. In the direct compression method, there are often problems related to content uniformity so that optimization is needed, both at the mixing stage of the powder mass and tabletting stage. The research was initiated by developing and validating the analytical method using reverse phase high performance liquid chromatography (HPLC). The optimal mixing is determined by plotting the relative standard deviation (RSD) against time with the terms < 5%. Mixing the powder mass is divided into 3 stages. Stage I and II require a minimum mixing time of 20 minutes each, while stage III there is no significant difference between the test time and the homogeneity of the mixing. Optimization of tableting process was carried out for mixing stage III and main pressure scale on physical description, dissolution, hardness, content uniformity, disintegration time, assay, friability, and weight. The mixing time parameter in stage III has a significant effect on the dissolution result, while the main pressure scale has an effect on the dissolution result, hardness, and disintegration time. Based on the results of tabletting optimization, the mixing time of stage III in the range of 2 to 5 minutes and the main pressure scale in the range of 36 - 38 can be used.